Integrated spatial analysis of gene mutation and gene expression for understanding tumor diversity in formalin-fixed paraffin-embedded lung adenocarcinoma - Yamazaki, Miki; Hosokawa, Masahito; Matsunaga, Hiroko; Arikawa, Koji; Takamochi, Kazuya; Suzuki, Kenji; Hayashi, Takuo; Kambara, Hideki; Takeyama, Haruko (Frontiers in Oncology, 2022)
Introduction: A deeper understanding of intratumoral heterogeneity is essential for prognosis prediction or accurate treatment plan decisions in clinical practice. However, due to the crosslinks and degradation of biomolecules within formalin-fixed paraffin-embedded (FFPE) specimens, it is challenging to analyze them. In this study, we aimed to optimize the simultaneous extraction of mRNA and DNA from micro-dissected FFPE tissues (φ = 100 µm) and apply the method to analyze tumor diversity in lung adenocarcinoma before and after erlotinib administration. Method: Two magnetic beads were used for the simultaneous extraction of mRNA and DNA. The decrosslinking conditions were evaluated for gene mutation and gene expression analyses of micro-dissected FFPE tissues. Lung lymph nodes before treatment and lung adenocarcinoma after erlotinib administration were collected from the same patient and were preserved as FFPE specimens for four years. Gene expression and gene mutations between histologically classified regions of lung adenocarcinoma (Pre-treatment tumor in lung lymph node biopsies and post-treatment tumor, normal lung, tumor stroma, and remission stroma, in resected lung tissue) were compared in a microdissection-based approach. Results: Using the optimized simultaneous extraction of DNA and mRNA and whole-genome amplification, we detected approximately 4,000 to 10,000 expressed genes and the epidermal growth factor receptor (EGFR) driver gene mutations from micro-dissected FFPE tissues. We found the differences in the highly expressed cancer-associated genes and the positive rate of EGFR exon 19 deletions among the tumor before and after treatment and tumor stroma, even though they were collected from tumors of the same patient or close regions of the same specimen. Conclusion: Our integrated spatial analysis method would be applied to various FFPE pathology specimens providing area-specific gene expression and gene mutation information.